The hands of Orlac - Renard, Maurice 1875-1939 (Eureka Entertainment, 2021)
"Einem Pianisten, der bei einem Zugunglück seine Hände verloren hat, werden die Hände eines hingerichteten Raubmörders transplantiert. Fortan wird er von panischen Angstzuständen heimgesucht, die erst ein Ende finden, als er ein teuflisches Komplott aufdecken kann. Spätexpressionistischer Stummfilm, der realistische Kriminalfilm-Motive mit Elementen der seinerzeit noch jungen Wissenschaft der Psychologie verbindet und damit die Bewusstseinslage der unsicheren 20er-Jahre zum Ausdruck bringt. Ein beeindruckendes Spiel mit Licht und Schatten." [filmdienst.de]
Original: Österreich 1924
Special Blu-ray edition: 1080p presentation on Blu-ray from a restoration of the original film elements by @FILMARCHIV AUSTRIA. ; LPCM 2.0 score by Johannes Kalitzke ; original German language intertitles with optional English subtitles ; feature length audio commentary with author Stephen Jones and author / critic Kim Newman ; "Extremities" - video essay by filmmakers David Cairns & Fiona Watson ; alternate presentation of "The hands of Orlac" [SD, 110 minutes] - courtesy of the F. W. Murnau Foundation, a presentation of the film struck from a different print source, featuring alternate takes of certain scenes. Includes a musical score by Paul Mercer ; version comparison featurette ; plus: a collector's booklet featuring new essays by Philip Kemp and Tim Lucas
Bildformat 1.33:1
Keywords: Film; Blu-Ray-Disc